Pengaruh Sikap, Norma Subyektif dan Kontrol Perilaku yang Dirasakan Terhadap Niat Beli Pupuk Petroganik di Kabupaten Boyolali - Novitasari Dika Kusuma Dewi; Eny Lestari; Heru Irianto (Universitas Sebelas Maret, 2018)
This research aims to find out the effects of product attributes, environmental awareness, the cost of fertilizer usage, subjective norms to the attitude of Petroganik fertilizer purchases also to find out the effects of attitude, subjective norms and cost of fertilizer usage to the intentions of purchasing Petroganik fertilizer. The method used in this research is explanatory methods by using survey techniques. Method taken to determine research location was conducted purposively and this research is done in Nogosari District and Musuk District. The method used for gathering samples with multi stage random sampling. Samples in this research were collected from 64 respondents split from 4 villages and 8 group farmers. The technique of collecting data was solved through observation, interviews, and logging. The analysis of the sample data used for this research is Structural Equation Models (SEM) method and also Partial Least Square (PLS) as an altiernative method. The research finds that (1) product attributes and environmental awareness positively determinants of purchase attitudes. (2) subjective norms, purchase attitudes, and cost of fertilizer usage affects the purchase intentions for Petroganik fertilizer.